Chronic constipation and the brain-gut-microbiome axis: the role of 5-HT signaling and Traditional Chinese Medicine in pathophysiology and treatment - Zhang, Shuangshuang; Song, Xiao; Wen, Yan; Wang, Guosheng (Frontiers in Medicine, 2026)
Chronic constipation (CC) is a prevalent functional gastrointestinal disorder involving complex interactions among the brain-gut-microbiome axis, with 5-hydroxytryptamine (5-HT) as a key signaling node. Aberrations in 5-HT synthesis, release, receptor expression, or reuptake disrupt gastrointestinal motility, contributing to CC pathogenesis. Traditional Chinese Medicine (TCM), including herbal compounds, monomers, acupuncture, and tuina, exerts therapeutic effects by modulating the 5-HT signaling pathway. Animal studies demonstrate that TCM interventions regulate gut microbiota, promote 5-HT production via metabolites like short-chain fatty acids (SCFAs) and bile acids, and target receptors (e.g., 5-HT3R, 5-HT4R) to enhance intestinal motility. Clinical trials validate TCM’s efficacy in normalizing 5-HT levels and improving symptoms, with advantages in safety and holistic regulation. However, important gaps remain, including incomplete understanding of upstream and downstream 5-HT signaling mechanisms, paradoxical 5-HT expression, and limited investigation of comorbid emotional disorders. Future studies should explore how TCM interventions modulate the gut microbiota–5-HT axis and inflammation-related pathways to provide novel insights into CC management.